Labor Candidate Information Presentation on PT.Nusakita Cemerlang using PHP and MySQL - Indriyani Indriyani; Ir. Fitri Sjafrina, MM (Jurnal Sistem Informasi, 2009)
Currently the use of computer is mostly done by the company or organization is asdata storage media and information. One such utilization, the authors create adatabase in the form of presenting information to assist prospective workers HRD inconducting recruitment.PT. Nusakita Cemerlang is a manpower outsourcing company, where the companyprovides outsourced workers who are skilled, educated, and trained in accordancewith the needs of the client / customer. Currently the database of existing prospectiveworkers are still stored in the HRD manual. This will complicate the search processof HRD in a quality workforce with a short time and frequent labor kerangkapanprospective data for two different jobs.From the description above, the authors propose to provide a translation of themanual data storage to be computerized. This is expected to help the HRD in theprocess of information seeking candidates for employment and current job vacancies.We make this database is expected to help HRD at PT. Nusakita Cemaerlang in therecruitment of new candidates for employment.